Secondary analysis and participation of those at the data source - Merson, L; Guerin, P; Barnes, K; Ntoumi, F; Gaye, O (Elsevier, 2018)
Your Editorial Closing the door on parachutes and parasites (June 2018) offers poignant insight on key issues in authorship of manuscripts resulting from secondary data analysis. As global health researchers who believe in the ethical and scientific imperative to maximise health gains from existing data, we strongly support the need to get this right. The discourse is not only important to develop sound publication practice, but also to promote equity, effectiveness, and sustainability of global health research collaboration. We agree that policy on academic authorship must evolve to avoid undermining these objectives.